Evaluation of Probiotic potentials of cheese isolate L. plantarum C6 - Hati, Subrota; Vij, Shilpa (Indian Journal of Dairy Science, 2014)
Probiotic potentials of L. plantarum C6 were evaluated through in vitro studies. Cheese isolate L. plantarum C6 culture showed maximum probiotic potentials (acid tolerance, bile tolerance, cell autoaggregation, cell surface hydrophobicity, antibiotic susceptibility, antimicrobial and antioxidative activity). In the present study, L. plantarum C6 exhibited highest viable counts against acid tolerance or low pH tolerance (at pH 3 after 2hrs of incubations), bile tolerance (conc. 1%), cell surface hydrophobicity against O-Xylene (39.24%), antimicrobial activity against B. cereus (zone of inhibition: 23.67mm), antioxidative activity (55.67% inhibition) following standard test methods suggested by various research workers.